2019
DOI: 10.3389/fcell.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Signaling in Cancer: Lessons From Drosophila Models

Abstract: Hippo pathway was initially identified through genetic screens for genes regulating organ size in fruitflies. Recent studies have highlighted the role of Hippo signaling as a key regulator of homeostasis, and in tumorigenesis. Hippo pathway is comprised of genes that act as tumor suppressor genes like hippo ( hpo ) and warts ( wts ), and oncogenes like yorkie ( yki ). YAP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 206 publications
(297 reference statements)
1
56
0
Order By: Relevance
“…Since the seminal identification of the Hippo pathway, multiple upstream regulators and downstream targets have been identified that implicate the core Hippo signaling pathway, comprised of Hippo kinase, Warts kinase, Mats (Mob1), and Salvador, as a key regulator for a diverse set of cellular and physiological functions, including stem cell maintenance, cellular differentiation, epithelial cell mechano-transduction, cytoskeletal dynamics, cell migration, organogenesis, tissue homeostasis, and pathology (reviewed in Staley and Irvine, 2012;Matsui and Lai, 2013;Yu and Guan, 2013;Irvine and Harvey, 2015;Fallahi et al, 2016;Chen et al, 2019;Sahu and Mondal, 2019;Snigdha et al, 2019). In this section, we focus only on the specific studies that identified the genes and illuminated our understanding of the signaling pathways.…”
Section: Fly Warts Ndr Kinase Is Central To the Highly Conserved Hippmentioning
confidence: 99%
“…Since the seminal identification of the Hippo pathway, multiple upstream regulators and downstream targets have been identified that implicate the core Hippo signaling pathway, comprised of Hippo kinase, Warts kinase, Mats (Mob1), and Salvador, as a key regulator for a diverse set of cellular and physiological functions, including stem cell maintenance, cellular differentiation, epithelial cell mechano-transduction, cytoskeletal dynamics, cell migration, organogenesis, tissue homeostasis, and pathology (reviewed in Staley and Irvine, 2012;Matsui and Lai, 2013;Yu and Guan, 2013;Irvine and Harvey, 2015;Fallahi et al, 2016;Chen et al, 2019;Sahu and Mondal, 2019;Snigdha et al, 2019). In this section, we focus only on the specific studies that identified the genes and illuminated our understanding of the signaling pathways.…”
Section: Fly Warts Ndr Kinase Is Central To the Highly Conserved Hippmentioning
confidence: 99%
“…While in the current work, we clari ed the miR-103a mimic lowered the extent of YAP phosphorylation in NSCLC cells, indicating a correlation between miR-103a and the Hippo signaling pathway. YAP, a related mammalian homolog of Drosophila yorkie that acts as an effector of the Hippo signaling pathway, is often induced in malignancies and may exerted tumor-promoting properties by activating CSCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…The first mutant component of the Hpo pathway, wts, was retrieved from a forward genetic screen seeking tumor suppressors, with hpo, sav and mats being later identified based on the same phenotype of tissue overgrowth in mosaic mutant clones (Justice et al, 1995;Xu et al, 1995;Kango-Singh et al, 2002;Tapon et al, 2002;Harvey et al, 2003;Jia et al, 2003;Pantalacci et al, 2003;Lai et al, 2005;Zheng and Pan, 2019). Two of these components, hpo and wts, encode a serine/threonine kinase that belongs to the Ste-20 kinases and Nuclear Dbf2-related (NDR) family of proteins, respectively (Snigdha et al, 2019). Further studies have shown that the Hpo and Wts proteins both bind to the WW domain adaptor protein, Sav.…”
Section: Components and Regulation Of Hippo Signalingmentioning
confidence: 99%